The Impact of Adverse Childhood Events on the Sexual and Mental Health of Women Experiencing Intimate Partner Violence - Willie, Tiara C. (Journal of interpersonal violence, 2021)
Women experiencing intimate partner violence (IPV) are at an increased risk of engaging in sexual risk behaviors and experiencing depressive and posttraumatic stress symptoms. Adverse childhood events (ACEs) can put women at increased risk of poor sexual and mental health. Women experiencing IPV report ACEs, but few studies have examined the heterogeneity in women’s experiences of ACEs and its effects on sexual and mental health. Therefore, the current study used latent profile analysis to identify profiles of ACEs (i.e., witnessing maternal and paternal IPV victimization; childhood physical, sexual, and emotional abuse; and physical and emotional neglect) and their association with sexual risk behaviors and depressive and posttraumatic stress symptoms. Women experiencing IPV aged 18 to 58 years (N = 212) were recruited from community establishments and completed face-to-face, computer-assisted interviews. Three profiles were identified: Low ACEs class (n = 115), Moderate ACEs class (n = 62), and High ACEs class (n = 35). Path analyses revealed that profiles of ACEs directly predicted women’s IPV victimization severity and depressive and posttraumatic stress symptoms. Secondary and tertiary mental health interventions may be more effective if the heterogeneity in women’s ACEs is addressed by integrating intervention strategies specific to these ACE subgroups.